The correlation between metabolic syndrome and calcium urolithiasis - Abdulla, Adil; Das, Shanmugha; V., Venugopalan A.; T., Rajeevan A.; M., Manikandan (International Surgery Journal, 2023)
Background: Urolithiasis affects about 12% of the global population. This study helps us to find the correlation between metabolic syndrome, its components and the risk of calcium stone urolithiasis. Methods: A cross-sectional study was conducted on 140 patients who underwent surgery for urolithiasis and whose stones were calcium-containing. A group of subjects who never had a history of urolithiasis was taken as control. Various anthropometric and biochemical parameters were studied to estimate and compare the prevalence of metabolic syndrome in both the groups. Results: The study showed that the central obesity of the study population was higher. However, even though prevalence of hypertension was more in the stone group compared to the control population, this difference was not statistically significant. On analysis of biochemical parameters like fasting blood sugar, triglycerides and HDL, abnormal triglycerides and HDL were significantly higher in the stone group when compared to the control. On consideration of all parameters as per international diabetes federation (IDF) definition, prevalence of metabolic syndrome in stone group was 40% which was higher than the control group with 25% and the difference was statistically significant. While summing up the number of parameters of metabolic syndrome an individual has in each group it is evident that the proportion of patients in the stone group had a greater number of parameters compared to the control group. Conclusions: This study could conclude that there is a significant correlation between calcium urolithiasis and metabolic syndrome.